Persepsi Akademisi Muslim Di Kota Metro Terhadap Ajaran Mendirikan Negara Islam - Santoso, Dri; Nasrudin, Muhamad (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Abstract: this article studies the perception of muslim academia in the City of Metro on the idea of establishing Islamic state in Indonesia. This study involves academia fro four universities in Metro two of which are affiliated to Islamic organization of Nahdlatul Ulama and Muhammadiyah, whereas the rest two are not affiliated to any Islamic organization. Academia in this study hold important positions in campus as well as in community, interviews are conducted for the study. The study shows that the majority of academia believe that establishing Islamic state in Indonesia is not a religious obligation because islam does not clearly oblige it they believe that the current establishment of Indonesian nation-state as final and ideal for Indonesian context. However, they are sharply divided concerning implementing sharia. While some refuse it on the ground of religious plurality in Indonesia, others firmly support sharia as part of local aspiration. Key words: muslim academia, Islamic state, Indonesia